SYBERYJSKA PERSPEKTYWA DROGI DO ROSJI MICKIEWICZA. O OBECNOŚCI (?) SACRUM W POLSKICH I ROSYJSKICH ODCZYTANIACH UTWORU - Skalińska, Ewangelina (Colloquia Litteraria, 2019)
“A Syberian Perpective in Mickiewicz’s «Droga do Rosji» («The Road to Russia»). On the presence of the Sacred in polish and russian Interpretations of the poem” This paper, using the tools of Translation Studies, analyses the chosen trans- lations of the first fragment of Mickiewicz’s introduction to Dziady cz. III (The Forefathers’ Eve, Part III) in the context of neutralization of its Christian issues. This text, since the nineteenth century, has been manipulated on by Russian translators, in such ways which have allowed them to stress current political and philosophical issues.